2018
DOI: 10.1093/jas/sky216
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eucalyptus oil and anise oil supplementation on rumen fermentation characteristics, methane emission, and digestibility in sheep1

Abstract: The objective of this study was to evaluate antimethanogenic activity of eucalyptus oil (EUC) and anise oil (ANI) in vitro and in vivo using sheep as a model. In vitro study was conducted using batch culture technique, each of EUC and ANI were added at 0, 50, 100, 200, or 400 mg/L of fermentation media with substrate containing 60% corn-based concentrate and 40% hay (DM basis). Total gas production (GP) linearly (P < 0.01) decreased with increasing ANI, whereas the GP was not affected with EUC addition. Supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Concomitantly with increased total SCFA concentrations, the digesta pH decreased in colon of goats fed HC and HC-SY diets. Previous studies have reported that feeding HC diets enhanced fermentation rates and decreased digesta pH in colon of goats [ 3 ] sheep [ 32 ] and cattle [ 33 ]. Moreover, linear increase in SCFA concentrations and the decrease in pH with number of days fed HC diet suggests that long term feeding with HC diet severely increase the fermentation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitantly with increased total SCFA concentrations, the digesta pH decreased in colon of goats fed HC and HC-SY diets. Previous studies have reported that feeding HC diets enhanced fermentation rates and decreased digesta pH in colon of goats [ 3 ] sheep [ 32 ] and cattle [ 33 ]. Moreover, linear increase in SCFA concentrations and the decrease in pH with number of days fed HC diet suggests that long term feeding with HC diet severely increase the fermentation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that feeding HC diets enhanced fermentation rates and decreased digesta pH in colon of goats [ 3 ] sheep [ 32 ] and cattle [ 33 ]. Moreover, linear increase in SCFA concentrations and the decrease in pH with number of days fed HC diet suggests that long term feeding with HC diet severely increase the fermentation [ 32 ]. Nevertheless, colonic fermentation pattern in goats fed Se supplemented HC diet showed no significant difference compared with those fed HC diet without Se supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…However, rape may comprise a much higher nitrogen and sulfur content than rye grass, possibly leading to elevated nitrous oxide emissions of the ruminants through fecal matter, depending on seasonal variations and growth conditions. Alternative feed additives, such as tannins, oils or fats may reduce methane emissions by up to 18 – 20% but must be carefully monitored to avoid negative health effects due to sudden introduction or over ingestion and availability may be limited or seasonal ( Liu et al, 2011 ; Kolling et al, 2018 ; Wang et al, 2018 ). Another promising feed additive is the seaweed Asparagopsis that has been shown to reduce methane emissions by up to 80% ( Machado et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is very well established that feeding high concentrate (HC) diets enhance fermentation rate which causes an increase in concentrations of fermentative acids with simultaneous decrease in digesta pH in rumen and hindgut of mammals (Tao et al, 2017;Wang et al, 2018).…”
Section: Colonic Fermentation Pattern and Lps Levelsmentioning
confidence: 99%